2008
DOI: 10.1080/09581590701881615
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and Aboriginal people in Australia: A review of the literature

Abstract: This paper provides a thematic review of the literature on cancer in Aboriginal people in Australia, focusing on experiences in diagnosis, treatment and care as well as addressing sociocultural factors to guide the public health response to poorer treatment outcomes. A search of both medical and social scientific databases for journal articles published between 1995 and 2006 show that cancer incidence and possibly survival and mortality data are likely to be underestimated in Aboriginal people. Aboriginal peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…Aboriginal Australians between 45 and 64 are significantly more likely to die from cancer than non-Aboriginal Australians (Australian Institute of Health and Welfare 2011a). Clinical and epidemiological attention to these issues began to be made visible in the 1990s and early 2000s (e.g., Condon et al 2003;Veroni, Gracey, and Rouse 1994), gaining increasing prominence in the last few years (e.g., Garvey et al 2011;Newman et al 2008;Supramaniam, Grindley, and Pulver 2006). Research from New Zealand has also shown that survival from cancer is lower among the Māori people of that country (Hill et al 2010).…”
Section: Introductionmentioning
confidence: 95%
“…Aboriginal Australians between 45 and 64 are significantly more likely to die from cancer than non-Aboriginal Australians (Australian Institute of Health and Welfare 2011a). Clinical and epidemiological attention to these issues began to be made visible in the 1990s and early 2000s (e.g., Condon et al 2003;Veroni, Gracey, and Rouse 1994), gaining increasing prominence in the last few years (e.g., Garvey et al 2011;Newman et al 2008;Supramaniam, Grindley, and Pulver 2006). Research from New Zealand has also shown that survival from cancer is lower among the Māori people of that country (Hill et al 2010).…”
Section: Introductionmentioning
confidence: 95%
“…While a 2008 review of the literature argued that an understanding of Aboriginal people's experience of cancer must take account of the social, economic and cultural context of people's lives (Newman, Butow et al 2008), there has been little work which focuses on the intersection of these issues with health policy and service delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Indigenous Australians might be reluctant to seek aggressive cancer treatments such as surgery or chemotherapy if they are unable to continue with personal responsibilities given the lifestyle impacts or they might view other social and economic aspects of their life as more important than health. 26 People's views on health can be influenced by their culture which may also influence the decision to seek health care. For example, cancer can raise feelings of shame and fear for an Indigenous…”
Section: Culture and Health Decisionsmentioning
confidence: 99%
“…23,26 The Indigenous definition of being healthy includes the ability to continue with social and family responsibilities. Indigenous Australians might be reluctant to seek aggressive cancer treatments such as surgery or chemotherapy if they are unable to continue with personal responsibilities given the lifestyle impacts or they might view other social and economic aspects of their life as more important than health.…”
Section: Culture and Health Decisionsmentioning
confidence: 99%
See 1 more Smart Citation